Bear Island : the war at Sugar Point - Vizenor, Gerald Robert, 1934- (Indigenous Americas., 2006)
Drawing on the traditional ways of Anishinaabe storytelling, acclaimed writer Gerald Vizenor illuminates the 1898 battle at Sugar Point in this epic poem. Fought between the Pillagers of the Leech Lake Reservation and U.S. soldiers, the battle marked a turning point in relations between the government and Native Americans. Bear Island brings back to light a key moment in Minnesota's history.